High Purity/Recovery Separation of Propylene from Propyne Using Anion Pillared Metal-Organic Framework: Application of Vacuum Swing Adsorption (VSA) - Majeda Khraisheh (1349376) (2021)
Propylene is one of the world’s most important basic olefin raw material used in the production of a vast array of polymers and other chemicals. The need for high purity grade of propylene is essential and traditionally achieved by the very energy-intensive cryogenic separation. In this study, a pillared inorganic anion SIF62− was used as a highly selective C3H4 due to the square grid pyrazine-based structure. Single gas adsorption revealed a very high C3H4 uptake value (3.32, 3.12, 2.97 and 2.43 mmol·g−1 at 300, 320, 340 and 360 K, respectively). The values for propylene for the same temperatures were 2.73, 2.64, 2.31 and 1.84 mmol·g−1, respectively. Experimental results were obtained for the two gases fitted using Langmuir and Toth models. The former had a varied degree of representation of the system with a better presentation of the adsorption of the propylene compared to the propyne system. The Toth model regression offered a better fit of the experimental data over the entire range of pressures. The representation and fitting of the models are important to estimate the energy in the form of the isosteric heats of adsorption (Qst), which were found to be 45 and 30 kJ·Kmol−1 for propyne and propylene, respectively. A Higher Qst value reveals strong interactions between the solid and the gas. The dynamic breakthrough for binary mixtures of C3H4/C3H6 (30:70 v/v)) were established. Heavier propylene molecules were eluted first from the column compared to the lighter propyne. Vacuum swing adsorption was best suited for the application of strongly bound materials in adsorbents. A six-step cycle was used for the recovery of high purity C3H4 and C3H6 The VSA system was tested with respect to changing blowdown time and purge time as well as energy requirements. It was found that the increase in purge time had an appositive effect on C3H6 recovery but reduced productivity and recovery. Accordingly, under the experimental conditions used in this study for VSA, the purge time of 600 s was considered a suitable trade-off time for purging. Recovery up to 99%, purity of 98.5% were achieved at a purge time of 600 s. Maximum achieved purity and recovery were 97.4% and 98.5% at 100 s blowdown time. Energy and power consumption varied between 63–70 kWh/ton at the range of purge and blowdown time used. The VSA offers a trade-off and cost-effective technology for the recovery and separation of olefins and paraffin at low pressure and high purity. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/en14030609